2022
DOI: 10.3164/jcbn.21-67
|View full text |Cite
|
Sign up to set email alerts
|

State of anxiety may be associated with exocrine pancreatic insufficiency in functional dyspepsia patients with pancreatic enzyme abnormalities

Abstract: We have reported that refractory functional dyspepsia patients with pancreatic enzyme abnormalities (FD-P). We tried to analyze the prevalence of exocrine pancreatic insufficiency (EPI) in FD-P patients to clarify whether the pathophysiology of FD patients including clinical symptoms and quality of life were associated with EPI. We enrolled forty-nine patients presenting with typical symptoms of FD-P patients (n = 20) and asymptomatic patients with pancreatic enzyme abnormalities (AP-P) (n = 29). Five pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Diagnosis of FD-P patients based on no abnormal findings on upper GI endoscopy, abdominal US, and CT scan could not be completely excluded ECP patients without endosonography. In addition, in our data, exocrine pancreatic dysfunction in patients with FD-P was widely observed as well as previous study [ 33 , 34 ]. Exocrine pancreatic function is regulated by gut hormones such as CCK and 5-HT [ 35 , 36 ] and is associated with gastric emptying [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Diagnosis of FD-P patients based on no abnormal findings on upper GI endoscopy, abdominal US, and CT scan could not be completely excluded ECP patients without endosonography. In addition, in our data, exocrine pancreatic dysfunction in patients with FD-P was widely observed as well as previous study [ 33 , 34 ]. Exocrine pancreatic function is regulated by gut hormones such as CCK and 5-HT [ 35 , 36 ] and is associated with gastric emptying [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…our data, exocrine pancreatic dysfunction in patients with FD-P was widely observed as well as previous study [33,34]. Exocrine pancreatic function is regulated by gut hormones such as CCK and 5-HT [35,36] and is associated with gastric emptying [37,38].…”
Section: Plos Onesupporting
confidence: 80%
“…In this study, patients with FD‐P also significantly exhibited epigastric pain and early satiety following fat intake compared with patients with FD. Considering that patients with FD‐P exhibit almost 60% of exocrine pancreatic dysfunction, 21 fat intake‐related gut hormones such as CCK and GLP‐1 may aggravate clinical symptoms such as epigastric pain and early satiety following high‐fat meals in Japanese patients with FD‐P. In contrast, in Singaporean populations, patients with FD‐P also exhibit epigastric pain and early satiety following high‐fat meals, albeit insignificantly.…”
Section: Discussionmentioning
confidence: 98%
“…We reported that physical quality of life in patients with FD‐P was significantly different from that in patients with FD in Japan. Our previous study reported that exocrine pancreatic function in patients with FD‐P was significantly impaired compared with the asymptomatic patients with pancreatic enzyme abnormalities 21 . Because exocrine pancreatic insufficiency is regulated by factors such as CCK, GLP‐1, 5‐HT, as well as the vasovagal pathway system, 24–26 physical quality of life in patients with FD‐P may be easily impaired by external stress through the disturbed vasovagal pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation